The Transformation from Leader to Intrapreneur: Exploratory Study for the Theoretical Bridge between Leadership and Entrepreneurship - Haruomi SHINDO; Yasushi FUKUHARA (AAOS Transactions)
In existing firms, the transformation from a leader of an established company to an intrapreneur takes place in the development of new ventures. To explain this management phenomenon, it is necessary to construct a theoretical model that bridges entrepreneurship and leadership. The purpose of this study is to identify the issues involved in researching the transformation from leader to intrapreneur. As research methods for this purpose, this study conducts （1） a comparative analysis of journals and keywords by searching article databases and （2） a review of previous studies. The presented frame of the transformation from leader to intrapreneur includes at its core the attitudes, characteristics, behaviors, and outcomes of intrapreneurs, as well as organizational factors that influence intrapreneurs, some organizational outcomes, and entrepreneurial middle management. In addition, organizational structure, organizational culture, organizational change, and transformational leadership are outside of the leader-to-intrapreneur transformations. The implications of this study are （1） that it identifies the issues related to the leader-to-intrapreneur transformation and （2） that it bridges the research areas of entrepreneurship and leadership. The limitations of this research include the fact that the causal relationships between the factors have not been demonstrated, and the mechanism of leader-to-intrapreneur transformation has not been clarified.